2016
DOI: 10.5114/aoms.2016.59937
|View full text |Cite
|
Sign up to set email alerts
|

Colonization of multidrug resistant pathogens in a hybrid pediatric cardiac surgery center

Abstract: IntroductionThe incidence of multidrug resistant microorganisms worldwide is increasing. The aim of the study was to present institutional experience with the multidrug resistant microorganism colonization patterns observed in children with congenital heart diseases hospitalized in a hybrid pediatric cardiac surgery center.Material and methodsMicrobiological samples were routinely collected in all children admitted to our department. All microbiological samples were analyzed with regard to multidrug resistant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
9
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 19 publications
4
9
0
2
Order By: Relevance
“…This finding is similar to those reported in colonization screening by other authors [20]. It could be interesting to discuss whether screening for MDRB in our setting should be done only with anal swab (just one site of sampling), with the objective of enhancing the cost-effectiveness of MDRB screening.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…This finding is similar to those reported in colonization screening by other authors [20]. It could be interesting to discuss whether screening for MDRB in our setting should be done only with anal swab (just one site of sampling), with the objective of enhancing the cost-effectiveness of MDRB screening.…”
Section: Discussionsupporting
confidence: 90%
“…We found 15% ESBL colonization, similar to a Polish study on the same population (16% MDRB) [20] and to a reported colonization rate in a 2012 report from France (15%) [22]. However, it was lower than those reported by Kim et al in a Korean study of intensive care unit patients (28.2%) [21]; in another recent Korean study, the authors reported a rate of 42.5% in ICU patients and 20.3% even in healthy persons [23].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…There is still a lack of definitive guidelines to provide proper antibiotic prophylaxis in children undergoing cardiac surgery, especially with relation to extracorporeal circulation [7,8]. There are many reasons why many discussions about limiting antibiotic use and the duration of prophylaxis in pediatric cardiac surgery still didn't led to precise guidelines, while several publications encourage cardiothoracic centers to consider a change [9].…”
Section: Discussionmentioning
confidence: 99%